Pancreatic phenotype in infants with cystic fibrosis identified by mutation screening. Issue 10 (20th April 2007) - Cipolli, Marco; Castellani, Carlo; Wilcken, Bridget; Massie, John; McKay, Karen; Gruca, Margie; Tamanini, Anna; Assael, Maurice Baroukh; Gaskin, Kevin
Abstract : Objective: To determine the pancreatic phenotype of infants with cystic fibrosis (CF) diagnosed in the first week of life by a combined immunoreactive trypsin/mutation screening program. Design: A prospective evaluation of pancreatic function in infants with CF at the time of neonatal diagnosis and up to the age of 12. Setting: Two different centres (Verona, Italy and Westmead, Australia) to enable comparison of results between two regions where <60% or ⩾90% of patients, respectively, have at least one single ΔF508 a mutation. Patients: 315 children with CF including 149 at Verona and 166 at Westmead. Interventions: Fat balance studies over 3–5 days and pancreatic stimulation tests with main outcome measures being faecal fat or pancreatic colipase secretion. Patients with malabsorption are pancreatic insufficient (PI) or with normal absorption and pancreatic sufficient (PS). Results: 34 infants (23%) at Verona and 46 (28%) at Westmead were PS at diagnosis. 15% of those with two class I, II or III "severe" mutations and 26/28 (93%) of those with class IV or V mutations were PS at this early age. Of the 80 infants with PS, 20 became PI before the age of 12. All 20 had two severe mutations. Conclusion: Neonatal mutational screening programs for CF are less likely to detect PS patients with non-ΔF508 mutations. Of PS patients who are detected, those with two severe class I, II or III mutations are at particularly high risk of becoming PI during early childhood.